OsHIPP17 is involved in regulating the tolerance of rice to copper stress - Shi, Yang; Jiang, Nan; Wang, Mengting; Du, Zhiye; Chen, Ji; Huang, Yanyan; Li, Mingyu; Jin, Yufan; Li, Jiahao; Wan, Jian; Jin, Xiaowan; Zhang, Lang; et al. (Frontiers in Plant Science, 2023)
Introduction Heavy metal-associated isoprenylated plant proteins (HIPPs) play vital roles in metal absorption, transport and accumulation in plants. However, so far, only several plant HIPPs have been functionally analyzed. In this study, a novel HIPP member OsHIPP17, which was involved in the tolerance to copper (Cu) was functionally characterized. Methods In this study, qRT-PCR, Yeast transgenic technology, Plant transgenic technology, ICP-MS and so on were used for research. Results OsHIPP17 protein was targeted to the nucleus. The Cu concentration reached 0.45 mg/g dry weight due to the overexpression of OsHIPP17 in yeast cells. Meanwhile, the overexpression of OsHIPP17 resulted in the compromised growth of Arabidopsis thaliana (Arabidopsis) under Cu stress. The root length of Oshipp17 mutant lines was also significantly reduced by 16.74- 24.36% under 25 mM Cu stress. The roots of Oshipp17 rice mutant showed increased Cu concentration by 7.25%-23.32%. Meanwhile, knockout of OsHIPP17 decreased the expression levels of OsATX1, OsZIP1, OsCOPT5 or OsHMA5, and increased the expression levels of OsCOPT1 or OsHMA4. Antioxidant enzyme activity was also reduced in rice due to the knockout of OsHIPP17. Moreover, the expression levels of cytokinin-related genes in plants under Cu stress were also affected by overexpression or knockout of OsHIPP17. Discussion These results implied that OsHIPP17 might play a role in plant Cu toxic response by affecting the expression of Cu transport genes or cytokinin-related genes. Simultaneously, our work may shed light on the underlying mechanism of how heavy metals affect the plant growth and provide a novel rice genetic source for phytoremediation of heavy metal-contaminated soil.